If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + 2y) + -1(4a + -3y) = 0 Remove parenthesis around (4a + 2y) 4a + 2y + -1(4a + -3y) = 0 4a + 2y + (4a * -1 + -3y * -1) = 0 4a + 2y + (-4a + 3y) = 0 Reorder the terms: 4a + -4a + 2y + 3y = 0 Combine like terms: 4a + -4a = 0 0 + 2y + 3y = 0 2y + 3y = 0 Combine like terms: 2y + 3y = 5y 5y = 0 Solving 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = 0 Simplifying y = 0
| 8(5x+6)=3(4-7) | | 4y^2+12y= | | x=.08*200 | | V+6x=X+W | | x=8*200 | | 7n-3=3n+15 | | x=y-90/4 | | 6-7x=11+31x | | 5x-3y=2xy-11 | | 8a=49 | | 3x+y^2=7 | | 5/7÷5/8= | | 4/5(3x/2-5) | | 4/5(3x/2-5)(10x-2) | | 49y^2-64=0 | | 3x/15x=9 | | 4z/9-1=1 | | cos(x)=2.625 | | cosx=2.625 | | 4/5(3x/2-5)(10x-2)=0 | | 6x/36=12 | | 8x-22=64+6x | | 5(4x-3)=2(2+6) | | 5*x+7=8 | | 15w-2(w+5)=11 | | 4xp=68 | | 9x+3=7x+45 | | 7X-3=4x+10+2 | | (x+5-3i)(x+5+3i)(x-2)(x-2)= | | 3/8r=-24 | | 4p-3=25 | | 5+3(5x-1)=32 |